Longitudinal assessment of the lung mechanics of very low birth weight preterm infants with and without bronchopulmonary dysplasia - Mello, Rosane Reis de; Silva, Kátia Silveira da; Costa, Anniele Medeiros; Ramos, José Roberto de Moraes (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Prematurity has been correlated with altered lung mechanics. Some infants develop lung injury as a consequence of lung immaturity, invasive mechanical ventilation and exposure to oxygen, thus resulting in bronchopulmonary dysplasia. The aim here was to compare the lung mechanics of preterm infants with and without bronchopulmonary dysplasia during the first year of life. DESIGN AND SETTING: Prospective cohort study in a tertiary-level hospital. METHODS: This study included premature infants at a public hospital who underwent two pulmonary function tests: one at discharge and the other at the corrected age of 4 to 8 months. Tidal volume, lung compliance and lung resistance were measured. Statistical tests were used for comparisons between in-fants with and without bronchopulmonary dysplasia. RESULTS: 102 children with mean gestational age of 29 ± 2.0 weeks were studied; 17 with bronchopul-monary dysplasia. Lung compliance (0.84 ± 0.29 versus 1.28 ± 0.46; P < 0.001) and tidal volume (6.1 ± 0.94 versus 7.2 ± 1.43; P < 0.01) at discharge were significant lower in children with bronchopulmonary dyspla-sia than in those without the disease, but no differences were observed at the second test (compliance: 1.53 ± 0.77 versus 1.94 ± 1.01; P = 0.12; and tidal volume: 6.9 ± 1.4 versus 7.3 ± 1.6; P = 0.42). CONCLUSION: Differences in lung mechanics were observed between infants with and without bron-chopulmonary dysplasia at hospital discharge but these differences were no longer detected at the final follow-up. The lung mechanics of all the infants improved over this period of time.